A wireless camera supervision robot (CSR-BOT) for the cylindrical pipes and cables surfaces observation - Muhammad Muhyiddin, Ahmad Haniff (2014)
Nowadays, the use of robots as an observer has been used for a variety of sectors. However, the use of robots to monitor the condition of high voltage cable is not yet widespread. As a result, the project aims to design and create a robot for monitoring a cable condition. In addition, the project will aid the use of manpower as cable condition monitor. There are various disadvantages of using manpower such as not monitoring the situation accurately and they may face with electromagnetic radiation which can minimize their health risk for a long term. This project is to develop a semi-automatic mobile robot that can move along through the overhead transmission line cable or any cylindrical pipes surfaces. The problem can be improved by using the Camera Supervision Robot (CSR-BOT), which can observe the cable from three different angles. This is because the CSR-BOT body is equipped with three webcam cameras. This is to ensure the handler could inspect the cable condition accurately. The live preview from the webcam camera during the inspection can be viewed, captured (image) and recorded (video) directly from laptop by using a simple Graphical User Interface (GUI) called “GUI-Interface for CSR-BOT” program. This program is able to record video in high quality AVI format while the images captured will be stored in the PNG file extension. Monitoring system of the robot is able to see the condition of the cables if there are any scratches, dust and rust. If there is any problem at the cable, it may affect performance of the electrical current flow through the conductors. CSR-BOT is also capable of withstanding the vibration resistance when tested horizontally or vertically. Based on the data taken, cable maintenance can be easily done because the distance of the damage cable can precisely know by the technician. In addition, the CSR-BOT can be used on cable size from 1cm to 2.5cm and can monitor the condition of the cables from three different angles of 0 ° -120 °, 120 ° -240 ° and 240 ° -360 °.